Pengembangan Teknologi Imaging untuk Pemantauan Parameter Opasitas Asap Hitam pada Cerobong Industri - Ahmad Maulana Syafii; Rifki Rifki Muheimin; Prakasa Prakasa (LPPM ITK, 2017)
The Increased industrial subsector in Indonesia each year have some negative impact on health in Indonesia. Exhaust emissions of industrial activities is one of the sources of air pollution that occurs continuously. Exhaust gas quality monitoring needs to be done regularly to control the level of air pollution as required under KepMenLH 13/1995. During the determination of the opacity of the black smoke chimney industry performed manually using Ringlemann. Results opasitasbergantung on the observer on the ground so that the level of accuracy obtained is still less opacity akurat. Paper is about the development of imaging technology for monitoring parameters of black smoke in the exhaust stack opacity industri.Metode measurement used in this monitoring is a method Ringlemann. Segmentation algorithm used in this research is using thresholding. The result of the automatic segmentation using thresholding sample data has a high degree of accuracy, but still dependent on weather conditions. If you do smoke segmentation when the sky is clear, the level of accuracy of the segmentation is very high, but it is different when overcast or cloudy weather conditions. Results from this study is the obtainment function to be able to determine the level of black smoke opacity parameter. Searches made through a logarithmic function. Determination of the proper function is determined by looking at the highest value of Rଶ. Different sky conditions lead to different functions, so the algorithm functions to determine the parameters of black smoke opacity made in some circumstances under the conditions of the sky.